Mathematics for Human Flourishing in the Time of COVID-19 and Post COVID-19 : Proceedings of the Workshop Held at the Faculty of Mechanical Engineering, University of Niš, Niš, 21 of October 2020 - Mahouton Norbert Hounkonnou; Melanija Mitrović (De Gruyter, 2023)
The International Chair in Mathematical Physics and Applications (ICMPA - UNESCO chair), University of Abomey-Calavi, Benin, and the Center for Applied Mathematics of the Faculty of Mechanical Engineering Niš, CAM-FMEN, organized a webinar on Mathematics for human flourishing in the time of COVID-19 and post COVID-19, 21 October 2020, supported by the City of Niš. The objectives of the webinar were to give precise information about the work that scientists do to cure the disease, to push forward technology, to understand our society and create new expressions of humanity, and to question the role of mathematics in the responses to this pandemic.